1969
DOI: 10.1177/000331976902000704
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology of the Subclavian Steal Syndrome

Abstract: The subclavian steal syndrome, at first angiographically observed by Co-torni7 in 160, and according to clinical experiments determined by Reivich et a1.2 in 1961, has expectedly gained practical importance in the past years. Up to now we have noticed some 203 publications and 386 cases described in the Anglo-American as well as German and French literature, of which information was given lately in a comprehensive summary.3 Up to now, the German literature has published some 27 compositions on subclavian steal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

1971
1971
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
10
0
4
Order By: Relevance
“…Angiography was the initial test used to screen for subclavian steal, with only high probability patients being investigated [6]. This selection bias in testing gave the false impression that SSS was not only rare, but also symptomatic [7].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Angiography was the initial test used to screen for subclavian steal, with only high probability patients being investigated [6]. This selection bias in testing gave the false impression that SSS was not only rare, but also symptomatic [7].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…The average age of patients with subclavian steal is 50-60 years (46,47) and there is a predominance in men (70%). The subclavian steal also occurs three times more often on the left side (47).…”
Section: Subcla Vian Stealsmentioning
confidence: 99%
“…About 77% of all patients suffer from occlusion and about 23% from stenosis. Of the total, about one half suffer from multiple vascular occlusions or stenoses (46,47) and 10% are hypertensive. Spontaneous improvement may occur in many cases (8), apparently due to the development of adequate collaterals.…”
Section: Subcla Vian Stealsmentioning
confidence: 99%
“…Tyras and Barney' 1 thus suggested that systolic pressure gradients of 60 mm Hg or greater are more commonly seen in symptomatic patients,11 but other series describe similar symptoms with systolic pressure gradients as low as 20 mm Hg. 35,36 In order to provide convincing documentation of our hypothesis, arteriograms must be made with good visualization of the internal mammary arteries and note made of direction of flow both at rest and during arm exercise. Full cardiologic evaluation must, of course, include arm3' as well as leg exercise EKG.…”
Section: Discussionmentioning
confidence: 99%